Electrospinning preparation and mechanical properties of PVA/HNTs composite nanofibers. (17th November 2016) - Cheng, Zhi‐Lin; Qin, Xi‐Xi; Liu, Zan; Qin, Dun‐Zhong
Abstract : In this paper, the PVA/HNTs composite nanofibers with well‐enhanced mechanical properties were successfully prepared by electrospinning technique. The structure and properties of the composite nanofibers were characterized by TEM, XRD, FT‐IR, and DSC. The results indicated that the highly oriented and dispersed HNTs wrapped in polymer matrix were achieved by inducing function during electrospinning processing. The mechanical properties of the PVA/HNTs composite nanofibers depended on HNTs content were investigated, which showed 72.4% increase in tensile strength at optimal filling content. Copyright © 2016 John Wiley & Sons, Ltd.